FM19G11-Loaded Gold Nanoparticles Enhance the Proliferation and Self-Renewal of Ependymal Stem Progenitor Cells Derived from ALS Mice - Marcuzzo, Stefania; Isaia, Davide; Bonanno, Silvia; Malacarne, Claudia; Cavalcante, Paola; Zacheo, Antonella; Laquintana, Valentino; Denora, Nunzio; Sanavio, Barbara; Salvati, Elisa; Andreozzi, Patrizia; Stellacci, Francesco; et al. (Cells (Basel, Switzerland), 2019)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease affecting motor neurons. In ALS mice, neurodegeneration is associated with the proliferative restorative attempts of ependymal stem progenitor cells (epSPCs) that normally lie in a quiescent in the spinal cord. Thus, modulation of the proliferation of epSPCs may represent a potential strategy to counteract neurodegeneration. Recent studies demonstrated that FM19G11, a hypoxia-inducible factor modulator, induces epSPC self-renewal and proliferation. The aim of the study was to investigate whether FM19G11-loaded gold nanoparticles (NPs) can affect self-renewal and proliferation processes in epSPCs isolated from G93A-SOD1 mice at disease onset. We discovered elevated levels of SOX2, OCT4, AKT1, and AKT3, key genes associated with pluripotency, self-renewal, and proliferation, in G93A-SOD1 epSPCs at the transcriptional and protein levels after treatment with FM19G11-loaded NPs. We also observed an increase in the levels of the mitochondrial uncoupling protein (UCP) gene in treated cells. FM19G11-loaded NPs treatment also affected the expression of the cell cycle-related microRNA (miR)-19a, along with its target gene PTEN, in G93A-SOD1 epSPCs. Overall our findings establish the significant impact of FM19G11-loaded NPs on the cellular pathways involved in self-renewal and proliferation in G93A-SOD1 epSPCs, thus providing an impetus to the design of novel tailored approaches to delay ALS disease progression.